2002
DOI: 10.1001/archsurg.137.11.1294
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Findings of Colorectal Liver Metastases Can Be Predictive for Recurrence After Hepatic Resection

Abstract: Background: We recently reported that the pathologic mode of infiltrative growth (infiltrative [INF]-␣, INF-␤, and INF-␥) of colorectal liver metastases had characteristic morphologic findings, and furthermore showed that the INF type was a prognostic factor for diseasefree survival after hepatic resection. Hypothesis: Preoperative computed tomographic (CT) findings of the liver nodules may be predictive for pathologic tumor growth pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Radiological imaging studies have revealed subgroups of liver metastases with different contrast enhancement and delineation, supporting the hypothesis of morphological heterogeneity (Yamaguchi et al, 2002).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Radiological imaging studies have revealed subgroups of liver metastases with different contrast enhancement and delineation, supporting the hypothesis of morphological heterogeneity (Yamaguchi et al, 2002).…”
mentioning
confidence: 68%
“…These tumours co-opt the blood vessels of the alveolar septa and are comparable to the liver metastases with a replacement growth pattern. Computed tomographic (CT) imaging of liver metastases has been shown to be predictive for recurrence after hepatic resection (Yamaguchi et al, 2002). CT contrast-enhanced images of liver metastases were subtyped according to the shape of the metastases and the irregularity of the outline of the nodules.…”
Section: Tumourmentioning
confidence: 99%
“…In a study by Lunevicius [8] that focussed on those tumours surrounded by desmoplastic stroma, it was suggested that local, but not distant, recurrence following liver surgery was lower in the desmoplastic group and that overall survival was greater in these patients, although this was not statistically significant. In another study, computed tomographic imaging of liver metastases has been shown to be predictive for recurrence after hepatic resection [9]. When liver metastases were subtyped according to the shape of the metastases and the irregularity of the outline of the nodules on the CT image, liver metastases with the most irregular shape and contour were predictive of reduced 5 year disease-free survival.…”
Section: Introductionmentioning
confidence: 94%
“…Histological factors, including resection margins and infiltrative growth pattern, have been found to be predictive of survival 12 ; however, these are not useful pre-operative criteria. Further prognostic indicators include CT determination of pathologic growth pattern, 38 cell-cycle proteins Rb and p53 expression, thymidylate synthase 39 and antiapoptotic protein mcl-1, 40,41 and perioperative detection of circulating cancer cells. 42 As medical science progresses, these may become more available and be incorporated into any predictive score; however, at present, these sophisticated investigations are unlikely to be readily available in daily clinical practice.…”
Section: Commentmentioning
confidence: 99%